Long-term exposure to polycyclic musk tonalide - A potential threat to juvenile zebrafish (Danio rerio)? - Cahova, Jana; Blahova, Jana; Plhalova, Lucie; Marsalek, Petr; Doubkova, Veronika; Hostovsky, Martin; Divisova, Lenka; Mares, Jan; Faggio, Caterina; Svobodova, Zdenka (Veterinarni medicina, 2023)
Polycyclic musk compounds are commonly used in personal care products to replace expensive natural fragrances. Due to their huge consumption, they have become a part of the aquatic environment. In the present study, a two-month exposure effect of tonalide on juvenile zebrafish (Danio rerio) was investigated. We determined the vitellogenin concentration to define the potential endocrine-disrupting effect of tonalide and also analysed selected indices to evaluate the induction of oxidative stress. The environmentally relevant concentration of tonalide (i.e., 500 ng/l) caused a significant decrease in the catalase activity (P < 0.05) and a significant increase (P < 0.05) in the lipid peroxidation. An increasing lipid peroxidation was also recorded for the highest concentration group tested (i.e., 50 000 ng/l). On the other hand, no significant changes were recorded in vitellogenin in all the exposed groups. Thus, based on these results, we have not demonstrated the endocrine-disrupting activity of tonalide in zebrafish. The results of the oxidative stress indices showed a significant impairment of the antioxidant defence after the two-month tonalide exposure, which could indicate part of the adaptive response to the tonalide toxicity.
Keywords: aquatic contamination; vitellogenin; oxidative stress; endocrine disruptor; personal care products